"Kaya sa batang bayi" a localized communication strategy for the girl rising campaign of spark Philippines - Villanueva, Justin Niel L. (2018)
This study is created to promote the active participation of children in gender emancipation activities and women empowerment programs. In order to achieve this, there must be a familiar and localized communication efforts that includes children?s constructs and reality on gender-related issues. Thus, this crafting of a localized communication strategy that aims to capture the children?s local narrative on gender equality and children?s participation into a materialized communication intervention programs. The study aimed to bridge the current communication gap of the SPARK! Philippine?s Girl Rising campaign to their target audience, the children, through localizing the global context of the campaign. This was done through integrating the children?s narrative in their current gender emancipation program. The study is motivated by the existing discrimination of women, especially young girls, towards legitimate participation in the public space. With the growing numbers of women groups formations in the country, there is a need to give the children the avenue to be considered as an active agent of change rather than a passive victim of gender inequality and gender-based violence. The study is a qualitative research that is composed of two parts, the participatory formative research and the communication strategy. The participatory formative research includes determining the current best communication efforts and practices of Samahan ng mga Pilipina para sa Reporma at Kaunlaran (SPARK) towards engagement with the Filipino children and finding out the construct of the organization about children?s participation in gender emancipation. A participatory research is also done with selected children in Davao city, who represents a certain sector in a community. The study aimed to determine the children?s constructs and viewpoints on gender emancipation and women empowerment and the role of children in gender emancipation programs like the Girl rising campaign, this is done through a Formative Dialogue Research, which is composed of three (3) parts: the Evaluation of the Film Screening and Gender Sensitivity Training Workshop. The Evaluation and Documentation of Experiences and Opinions of the Children, and lastly, The Exploration of Children?s Participation in Gender Emancipation. The study discussed the emerging constructs of girls and empowerment which young girls as Catalyst of Change, Young Girls as Household figures, and Young Girls as Catalyst of Change, Young Girls as Household figures, and Young Girls and the Sisterhood. These constructs were used as the key messages of the localized communication strategies which able to discuss and help contextualize the study in a child-centered and Filipino context-sensitive aspect to the communication strategy. Moreover, the communication strategies are also created as tailored to the emerging problems found in the S.W.O.T Evaluation of the organization?s campaign. Ultimately, this study further enhances the on-going banner program of SPARK and focus on the opportunity for the children to be participate on the global movement towards gender emancipation and women empowerment.